Using Polar H10 for Analyzing pulse and calories and Comparing Positions Of Iraqi Soccer League 2017 – 2018 - Kahmis, Ahmed; Hussein, Al-meer Haider (Journal of Physical Education, 2018)
Using Polar H10 for Analyzing pulse and calories and Comparing Positions Of Iraqi Soccer League 2017 – 2018 The importance of the study lies in studying each position in soccer using modern electronic devices through which one can identify heart rate, calories expenditure. The problem of the study lies in coaches using one training program for all players regardless of their positions’ uniqueness and re physical and physiological requirements. The study aimed at identifying some physiological indicators using Polar H10 of Iraqi soccer premier positions as well as identifying differences among positions in some physiological indicators using Polar H10. The researcher hypothesized variances in pulse and calories for Iraqi soccer premier positions as well as statistical differences among positions in pulse and calorie in soccer. The researcher used the descriptive method. The subjects were selected randomly from Al Telaba, Al Nefet and Amana Baghdad clubs. Five matches were analyzed for each position and each club reaching a total of fifteen matches for each position using Polar H10 for physiological indicators. The results showed clear variations between the positions in the pulse and calories variables.